Las contrataciones públicas como herramienta estratégica para mejorar la gestión administrativa en la Unidad de Gestión Educativa Local de Pataz - Rodriguez Rengifo, Carlos Manuel (2019)
This report aims to raise awareness of the importance of the appropriate use of tools in public procurement in the Local Educational Management Unit of Pataz, identify the causes that caused the Entity not to meet its programmed goals and the solutions that were They gave to reverse that problem. The instruments and economic theories used in its development were identified such as: consumer theory, preferences, restrictions, utility, consumption balance and auction theory that led to achieve a performance in line with market expectations. Finally, alternative solutions were proposed for the improvement of Public Contracting procedures in UGEL Pataz, which favorably affected User Areas so that they can comply with the activities and responsibilities acquired in the short term, applying the modern management optimization tools.